The accuracy of 2D transvaginal ultrasound in the diagnosis of benign endometrial pathology: a comparison between ultrasonography and hysteroscopy - Jagot, Khatija H (Department of Obstetrics and Gynaecology, 2019)
STUDY OBJECTIVE: To evaluate the diagnostic accuracy of transvaginal sonography compared to hysteroscopy in diagnosing benign endometrial pathology. DESIGN: Retrospective cross-sectional study. Canadian Task force classification II – 2 SETTING: Department of Gynaecology, Groote Schuur Hospital, Cape Town, South Africa. PATIENTS: Patients having an office hysteroscopy procedure between January 2014 and December 2016, with a record of a recent transvaginal ultrasound and endometrial histology were included in this study. All malignant cases were excluded. INTERVENTIONS: Transvaginal ultrasound, endometrial biopsy and office hysteroscopy. MEASUREMENTS AND MAIN RESULTS: A total of one hundred and forty two patients, pre- and postmenopausal, were included in this study. The most common indications for hysteroscopy were abnormal uterine bleeding and postmenopausal bleeding. Sensitivity, specificity, positive and negative predictive values were calculated for ultrasonography and hysteroscopy in diagnosing benign endometrial pathology by comparing them to histological diagnosis as gold standard. The most common pathologies identified at histology were polyps and fibroids. For those patients who had a normal endometrium at ultrasound (n=59), hysteroscopy revealed 33.9% polyps, 5.1% submucosal fibroids and 49.2% normal/atrophic endometrium. The remainder of these patients demonstrated proliferative or hyperplastic endometrium, suspicious endometrium and adhesions. For those patients who had a normal hysteroscopy (n=26), ultrasound demonstrated 7.7% polyps, 7.7% submucosal fibroids, 11.5% cystic areas, 3.9% no comment on endometrium and 69.2% normal endometrium. In diagnosing polyps, hysteroscopy had a higher sensitivity (78%) than ultrasound (37.3%). However, ultrasound had a higher specificity (85.5%), compared to that of hysteroscopy which was 71.1%. The negative predictive value of hysteroscopy for polyps was 81.9% and ultrasound, 65.7%. In the diagnosis of submucosal fibroids, ultrasound had a higher sensitivity than hysteroscopy but they both had similar specificity. Ultrasound and hysteroscopy had high negative predictive values and low positive predictive values. The combination of ultrasound and hysteroscopy did not improve sensitivity, PPV or NPV with a small decline in specificity. CONCLUSION: This study demonstrated that hysteroscopy was more accurate in the diagnosis of endometrial polyps than ultrasound with a higher sensitivity and negative predictive value. However hysteroscopy had a lower sensitivity when diagnosing submucosal fibroids.